2019
DOI: 10.1038/s41598-019-46110-1
|View full text |Cite
|
Sign up to set email alerts
|

FGF family members differentially regulate maturation and proliferation of stem cell-derived astrocytes

Abstract: The glutamate transporter 1 (GLT1) is upregulated during astrocyte development and maturation in vivo and is vital for astrocyte function. Yet it is expressed at low levels by most cultured astrocytes. We previously showed that maturation of human and mouse stem cell-derived astrocytes – including functional glutamate uptake – could be enhanced by fibroblast growth factor (FGF)1 or FGF2. Here, we examined the specificity and mechanism of action of FGF2 and other FGF family members, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 71 publications
2
29
1
Order By: Relevance
“…Fibroblast growth factors (FGFs) constitute a family of at least 20 secreted ligands with pleiotropic roles in the developing and mature CNS (192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203). Most FGF receptors (FGFRs) can respond to multiple FGF ligands (e.g.…”
Section: Fgf Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast growth factors (FGFs) constitute a family of at least 20 secreted ligands with pleiotropic roles in the developing and mature CNS (192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203). Most FGF receptors (FGFRs) can respond to multiple FGF ligands (e.g.…”
Section: Fgf Family Membersmentioning
confidence: 99%
“…This notion is highlighted in a recent article by Duong et al (196), in which the authors report FGF8 to function as cell fate switch that controls the differentiation of radial glial cells in the SVZ into neurons or astrocytes. Additional studies have demonstrated that FGFs regulate astrocyte morphogenesis, maturation, and function in both health and disease (197)(198)(199). For instance, in remyelinating lesions of MS, FGF-1 may act as a promoter of remyelination by an indirect mechanism that involves the induction of CXCL8 and LIF expression in astrocytes (204).…”
Section: Fgf Family Membersmentioning
confidence: 99%
“…An almost 70-fold increase in the expression level of elastin was observed from week 1 to week 2, followed by a decrease at week 4. One potential cause of this sharp decrease in the elastin expression level could be linked to bFGF production by the iECs in the engineered constructs (Savchenko et al, 2019). Previous studies have shown that free bFGF decreases the expression levels of elastin at the transcriptional level in culture (Rich et al, 1996).…”
Section: Dynamic Ecm Evolutionmentioning
confidence: 99%
“…FGF family uses Ras/MAPK, PI3, and PLCγ pathways ( Diez Del Corral and Morales, 2017 ), through which it helps for neuroprotection, cell survival, and neural differentiation during embryonic development, it is also linked with epileptogenesis, mood disorders and autoimmunity in the brain ( Turner et al, 2016 ). Compared to other types of FGF, FGF 2 not only increases the cell survival, but they also help the maturation of the astrocytes and alter glutamate transport by the astrocytes through interaction with glutamate transporter 1 in mouse ( Savchenko et al, 2019 ). By this effect, they contribute to neuroprotection in two ways, increasing cell survival and avoiding excitotoxicity induced by accumulated glutamate.…”
Section: Discussionmentioning
confidence: 99%